Scraper Conveyor Sprocket Tooth Sequence Images Acquisition Device based on Shape From Focus - Liu Yinchuan; Ding Hua; Li Ning (Jixie chuandong)
Due to the problems of complicated process，low accuracy and efficiency of the existing wear measurement method of scraper conveyor sprocket tooth，a sprocket tooth sequence images acquisition device is designed based on shape from focus.By controlling the movement module of the device，the axial and circumferential alignment between an industrial camera and a sprocket tooth is realized，then control the sprocket tooth radial stepping motor every step，collect a image，repeat the cycle 100 times.And the sequence images acquisition of the sprocket tooth is completed.Test results show that sequence images acquisition device can quickly acquire clear sequence images of the sprocket tooth and provide hardware support and image data samples for the sprocket wear measurement of the scraper conveyor.